ANALISIS PENYERAPAN TENAGA KERJA PADA SEMBILAN SEKTOR EKONOMI DI SUMATERA SELATAN - Ridwan Effendi (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2014)
This research is aim analysing whether there is positive relationship between the labor demand with the gross domestic product, and negative relationship between the labor demand with wages atthenine economic sector in the South Sumatera province. The data were obtained from the central statistics agency and Bappeda of South Sumatera province from 2005 to2013. The method used panel data regression analysis, which includes The best model, classical assumptions and criteria statistics. The results indicates that simultaneously GDP with wages have influential strong and significant against the labor demand. Partially GDP show positive and significant effect on the labor demand. While the wages tell negative and significant effect on the labor demand at the nine economic sectors in South Sumatera province.